Minimum temperature drives community leaf trait variation in secondary montane forests along a 3000-m elevation gradient in the tropical Andes - Llerena-Zambrano, Melissa (2021)
Background: Leaf functional traits (LFT) influence resource acquisition and are important for understanding ecosystem processes. Climate and land use are key filters of community composition and LFT, however, how the relative importance of these filter changes with elevation has been little studied in the Andes. Aims: To gain insight into the functional response of Andean forests to climate and disturbance in naturally regenerated forest stands. Methods: We measured leaf blade thickness (LBT), leaf area (LA), specific leaf area (SLA), and leaf dry matter content (LDMC) from 13 secondary forest communities, along a 3000-m elevation transect. We derived basal area-weighted mean community (CWM) trait values to assess the effect of climate and disturbance on the functional structure of regenerating tree communities. Results: Community LFT progressively shifted along the elevation gradient driven by changes in temperature and successional stages towards communities with thicker leaves with low SLA. Reduction in LDMC with elevation suggested that both succulence and sclerophylly were important strategies in these forests. Conclusions: Our findings reinforce the validity of LFT as a powerful predictor to explore the ecological strategies of tree species in climate scenarios. Warmer conditions could result in a shift from slower to faster resource acquisition strategies at higher elevations